Opening & emptying your mind - Eswaran, Vijay, Dato'; Balagtas,Chandravali Dasi; Munian, Maralikrishnan; VStudios ([S.l.] : VStudios, 2008)
A talk by Dato' Vijay Eswaran on euro Vcon Madrid 2006, 8th Anniversary Convention, 19-22 September 2006, at Sol Melia Castilla Hotel Madrid, Spain
Title from title screen
Euro Vcon Madrid 2006
Executive producer, Pathman Senathirajah
DVD format
Keywords: Multilevel marketing; Direct marketing